A look over the curricular policies for teacher's trainings programs in Brazil and Portugal during the transition from the 20th toward the 21st century | Um olhar sobre as políticas curriculares para formação de professores no Brasil e em Portugal na transição do século XX para o XXI - de almeida, laa (2013)
The curricular policies for teacher's trainings have been creating a focus of academic interest both in Portugal and Brazil. Howerver, many times they have been confined to the characterization and model analysis that define them. As it is considered pertinent to broaden these studies, the curricular policies for teacher's trainings, in Portugal and in Brazil, in their relation to the emergent curricular issues of Elementary Education/Secondary Education, in this century transition is discussed in this article. To that end, we take a cyclic perspective basis (Ball, 2006) and a recontextualizing of curricular policies which will be analyzed by the many society's contexts or by different groups. This way this research is insert in a national and internationaldebate of curricular policies for teacher's trainings programs. To discuss this topic we used the theoretical contribution of authors such as Pacheco (2003), Ball (2001), Dias e López (2006), among others. We have done a desk analysis of the Brazilian and Portuguese realities, where we could draft a theoretical-methodological path of current speeches' discussion in those realities. From this perspective, the curriculum legitimates the knowledge, indicating what is valid and perceived in society as such. So, each group fights for its place in the curriculum and how it is going to be referenced. It is in the curricular policies that we find the structure where the decisions are made, as a space for competition and a collision of interests in many contexts, having a complex, dynamic, conflictual and hybrid tension. We would like to stress that, in the educational field, for the last two decades of the end of last century, the word change gained strength and space in many scenarios of different societies, with the enhancement of new educational policies, to mobilize new curriculum organization systems' logic. And the similarities among the issues of curriculum policies, both on global and local scenarios, are that the reforms around these policies are presented from different perspectives, which come to answer the different economic, social, politic and cultural interests perspectives. These differences perspectives are produced by many contexts and realities, since the global space is, in its essence, a producer of heterogeneity. Therefore, there are different contexts and ways for the production of curricular policies, in Brazil and Portugal, both of which present different concepts and attitudes regarding the educational reform.